Dance of the Deodhas: Divine Possession, Blood Sacrifice and the Grotesque Body in Assamese Goddess Worship - Burley, Mikel (Religions of South Asia, 2019)
’Possession’ by a deity or spirit has been a prevalent phenomenon in many religious and cultural milieus, including those of South Asia. Yet it has frequently been neglected by Indologists and marginalized by elite religious authorities. Also underexplored have been forms of goddess worship in Northeast India, where Tantric Hinduism has been strongly influenced by non-Hindu indigenous traditions. Helping to fill these gaps, this article examines the Deodhani festival (also known as Manasa Puja) at the Kamakhya temple in Assam, the centrepiece of which is a prolonged dance by ’shamanistic’ deodhas, whom devotees claim to be possessed by deities that include several ferocious goddesses. Utilizing the concept of the ’grotesque body’ from theories of art and literature, and contextualizing the festival in relation to the broader background of the temple and to practices of possession elsewhere, the article illuminates the themes of divine possession, animal sacrifice and transgressive ritual.